GE_GERICHTE P/16510/2020 vom 9. Oktober 2023 - GE Cour de justice (2023)
VIOLENCE DOMESTIQUE;VOIES DE FAIT;CONTRAINTE(DROIT PÉNAL);CONCOURS IMPARFAIT;PRESCRIPTION;VIOLATION DE DOMICILE | CP.126.al1; CP.181; CP.186